Arranjo, descrição e difusão do patrimônio documental arquivístico da Universidade Federal do Rio Grande do Sul - Conrado, Flavia Helena (2014)
About to turn 80 and known as the best university of the country according to the General Courses Index (IGC), the Federal University of Rio Grande do Sul (UFRGS) has its origins with Higher Education Schools and Colleges, home of the Higher Education in Rio Grande do Sul, which started working in Porto Alegre in the late 19th century. Due to its academic excellence, UFRGS has produced and accumulated over the years a rich archival heritage. So this research's goal is to identify and to propose an arrangement system for this archival heritage through the digital platform ICA-AtoM to describe and disseminate finding aids guide and inventory. This research is justified by the condition of UFRGS as a higher education institution with a significant importance in the state scenario as a national institution, through education, research and extension developed by it. As theoretical ground for this research, were used references that contemplated the concept of cultural heritage linked with the identification of archival heritage in this context. Also were debated and put into context archives administration themes, as the identification of archives administration as a science, archival functions, emphasizing Arrangement, Description and Diffusion of archives. The context of this study was given through a brief UFRGS historic, of how the Documentation Division was structured and how the archival holdings are organized. This is an applied, descriptive, qualitative research and a case study. The data collection was made through direct observation, as well as bibliographic and documental research. With this study it was able to identify the archival document as archival heritage, to set an arrangement system for UFRGS's archival holdings, to make an archival description and diffusion through the creation of a guide and an inventory and to implement these finding aids on the ICA-AtoM software. As the developed product, there are the guide and inventory of the holdings in custody by the Documentation Division, indispensable instruments for access, conservation and diffusion of the archival heritage. Lastly, it is important to highlight the need to continue this work that was a pioneer in its context of application, and it should be amplified and reevaluated when necessary.